Role of Lysophosphatidic Acid in Neurological Diseases: From Pathophysiology to Therapeutic Implications - Simona Dedoni; Valeria Avdoshina; Maria C. Olianas; Pierluigi Onali (Frontiers in Bioscience-Landmark)
Lysophosphatidic acid (LPA), a bioactive lipid molecule, has been identified as a critical regulator of several cellular processes in the central nervous system, with significant impacts on neuronal function, synaptic plasticity, and neuroinflammatory responses. While Alzheimer’s disease, Multiple Sclerosis, and Parkinson’s disease have garnered considerable attention due to their incidence and socioeconomic significance, many additional neurological illnesses remain unclear in terms of underlying pathophysiology and prospective treatment targets. This review synthesizes evidence linking LPA’s function in neurological diseases such as traumatic brain injury, spinal cord injury, cerebellar ataxia, cerebral ischemia, seizures, Huntington’s disease, amyotrophic lateral sclerosis, Hutchinson-Gilford progeria syndrome, autism, migraine, and human immunodeficiency virus (HIV)-associated complications Despite recent advances, the specific mechanisms underlying LPA’s actions in various neurological disorders remain unknown, and further research is needed to understand the distinct roles of LPA across multiple disease conditions, as well as to investigate the therapeutic potential of targeting LPA receptors in these pathologies. The purpose of this review is to highlight the multiple functions of LPA in the aforementioned neurological diseases, which frequently share the same poor prognosis due to a scarcity of truly effective therapies, while also evaluating the role of LPA, its receptors, and signaling as promising actors for the development of alternative therapeutic strategies to those proposed today.